Nilai-Nilai Pendidikan Karakter dalam Buku Cerita Rakyat dari Jambi 2 dan Relevansinya terhadap Pembelajaran Bahasa Indonesia di SMP - Afifah, Rahayu; Fitrah, Yundi; D, Yusra (Universitas Batanghari Jambi, 2023)
This study describes the value of character education contained in the book folklore from Jambi , â€œCerita Rakyat dari Jambiâ€ and describes its relevance to learning Indonesian in junior high school. This research is in the form of a qualitative descriptive. The data of this research are the values of character education in folklore and the data source is the book Folklore with stories 1) Asal Usul Raja Negeri Jambi, 2) Asal Mula Nama Sungai Batanghari, 3) Dongeng Hantu Pirau, 4) Legenda Bujang Jambi, 5) DatukÂ Darah Putih, 6) Dongeng Si Kelingking, 7) Depati Sebelas, 8) Putri Tangguk. Data collection techniques using literature study. The results of this study indicate that. There are 16 character education including religious, honesty, tolerance, discipline, hard work, creative, independent, democratic, curiosity, nationality, loving the homeland, respect achievement, love ofÂ peace, care of environment, social care, and responsibility. The relevance is that it is appropriate to use Indonesian language learning in Basic Competence (KD) 3.15 to identify information about local fables/legends that are read and heard. There is a match between the existing stories and the Basic Competencies used in the 2013 curriculum for class VII Junior High School in instilling character education values.